Toward Better Outcomes for Families Through Innovative Dispute Resolution Programs in England. (18th July 2019) - Dare, Holly; Goodman, Carole; John, Rebecca; Parsons, Sarah
Abstract : This article explores and shares the learning from two of Cafcass' innovative dispute resolution pilot programs. The programs aim to improve outcomes for families against the backdrop of rising private law demand in England, while keeping the child at the center. The Positive co‐Parenting Programme pilot provides a structured intervention to reduce conflict and promote timely resolution for children and families in complex cases. The Support with Making Child Arrangements pilot explores whether the provision of a package of support to parents ahead of the first court hearing can help them come to safe agreements about their children without the need for court intervention. Key Points for the Family Court Community: Early indicators suggest that these pilot interventions are helping to improve the service we provide to families in England, through a more targeted and tailored approach. The Support with Making Child Arrangements pilot has started to identify important lessons for improving triage and gatekeeping to divert cases into interventions most suited to the needs of the family, at the earliest possible stage in proceedings. The Cafcass Positive co‐Parenting Programme has demonstrated the potential for a fast and effective intervention program for harmful conflict cases. Early indicators suggest the child's letter to the parents, and the parents' letter to the child, have been a powerful tool in initiating change between the parents. The article highlights the importance of working innovatively in the family court in England within the context of increasing demand and limited resources, whilst keeping the child at the center.